Peningkatan Kemampuan Koneksi Matematis dan Penurunan Kecemasan Siswa SD melalui Pembelajaran Problem Based Learning Berbantuan Game Edukasi Wordwall - Evendi Evendi; Mirunnisa Mirunnisa; Novianti Novianti (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Mathematics learning in elementary school emphasizes not only the mastery of concepts, but also the development of mathematical connection skills and the management of students' affective aspects, particularly math anxiety. This study aims to analyze the improvement of mathematical connection skills and the reduction of mathematics anxiety of elementary school students through the application of the Problem Based Learning (PBL) model assisted by the Wordwall educational game. The study used a quantitative approach with a quasy experimental design of the pretest-posttest control group type. The research subjects consisted of 50 grade IV students divided into experimental classes and control classes. The research instruments were in the form of mathematical connection ability tests and mathematical anxiety questionnaires. Data were analyzed using Mann-Whitney U, N-gain, and Spearman's rho correlations. The results showed that the mathematical connection ability of students who obtained PBL learning assisted by Wordwall was significantly higher than conventional learning. There is a significant relationship between mathematical connection ability and students' math anxiety. Thus, Wordwall-assisted PBL learning is effective in improving mathematical connection skills and contributes to reducing mathematics anxiety in elementary school students.